Subtropical thermal variation supports persistence of corals but limits productivity of coral reefs. Issue 1907 (17th July 2019) - McIlroy, Shelby E.; Thompson, Philip D.; Yuan, Felix Landry; Bonebrake, Timothy C.; Baker, David M.
Abstract : Concomitant to the decline of tropical corals caused by increasing global sea temperatures is the potential removal of barriers to species range expansions into subtropical and temperate habitats. In these habitats, species must tolerate lower annual mean temperature, wider annual temperature ranges and lower minimum temperatures. To understand ecophysiological traits that will impact geographical range boundaries, we monitored populations of five coral species within a marginal habitat and used a year of in situ measures to model thermal performance of vital host, symbiont and holobiont physiology. Metabolic responses to temperature revealed two acclimatization strategies: peak productivity occurring at annual midpoint temperatures (4–6°C lower than tropical counterparts), or at annual maxima. Modelled relationships between temperature and P:R were compared to a year of daily subtropical sea temperatures and revealed that the relatively short time spent at any one temperature, limited optimal performance of all strategies to approximately half the days of the year. Thus, while subtropical corals can adjust their physiology to persist through seasonal lows, seasonal variation seems to be the key factor limiting coral productivity. This constraint on rapid reef accretion within subtropical environments provides insight into the global distribution of future coral reefs and their ecosystem services.